Role of the ICT in Women Empowerment and Achieving SDGs: A Case Study of Women Labor Force in Developing Countries - Amna Noor; Zahid Asghar; Haroon Sarwar; Irfanullah Arfeen (Faculty of Economic and Business, 2021)
The aim of the study is to analyze the ways women are empowered through information and communication technology (ICT) and fostering the process of achieving the Sustainable Development Goals (SDGs). Women in developing countries are facing economic and social hardships and have limited access to ICT, which in turn translate into their lack of skills, lower literacy rate and restricted social engagement. Therefore, present study explores the role of ICT on women empowerment in 51 developing countries by conducting panel data modeling over the period of 2000-17. The study finds that ICT has significant and positive contribution on female labor force participation rate by Generalized Method of Moment (GMM). Control variables like GDP growth and government expenditure on education have positive and statistically significant role to enhance women empowerment. Findings of the study imply that the ICT has an impact on women empowerment and which helps in fostering the process of achieving SDGs 2030.